Tingkat Pemahaman Siswa dalam Pembelajaran Atletik Nomor Lari Jarak Pendek Kelas X SMA Negeri 1 Sukatani - Fahrul Furkon; Citra Resita; Hj. Ine Rahayu Purnamaningsih (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is motivated by the lack of understanding of students in the learning process, especially in learning material for short distance running athletics, of course having goals and objectives to be taken. This study aims to determine the level of understanding of students in athletic learning in the number of short distance running class X SMA Negeri 1 Sukatani. This study uses a quantitative approach, because it is used to process data in the form of numbers from the population or existing samples to arrive at research conclusions. The technique used in this research is a closed questionnaire which consists of a multiple choice test. The population in this study were all students of class X SMA Negeri 1 Sukatani with a total of 396 students. The sample used in this study used a random sampling technique which was calculated through the Slovin formula for research sampling. The sample is part of the population in the study. The data analysis used in this research is descriptive quantitative analysis. The results showed that the athletic learning of sprint numbers in class X SMA Negeri 1 Sukatani, with a total sample of 80 students and the overall percentage (36.25%) of the data on factors and indicators described above, that the level of student understanding in athletics learning sprint numbers for class X SMA Negeri 1 Sukatani can be categorized as "Enough".